The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0185579
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of early T cell cytokine production by arsenic trioxide occurs independently of Nrf2

Abstract: Nuclear factor erythroid 2-related factor 2 (Nrf2) is a stress-activated transcription factor that induces a variety of cytoprotective genes. Nrf2 also mediates immunosuppressive effects in multiple inflammatory models. Upon activation, Nrf2 dissociates from its repressor protein, Keap1, and translocates to the nucleus where it induces Nrf2 target genes. The Nrf2-Keap1 interaction is disrupted by the environmental toxicant and chemotherapeutic agent arsenic trioxide (ATO). The purpose of the present study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…As 2 O 3 exposure resulted in a significant Nrf2-independent inhibition of both mRNA and protein production of IFNγ, IL-2, and GM-CSF in splenocytes ( VanDenBerg et al, 2017 ). It has been also demonstrated that As 2 O 3 inhibited IFN-α secretion in plasmacytoid dendritic cells ( Ye et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As 2 O 3 exposure resulted in a significant Nrf2-independent inhibition of both mRNA and protein production of IFNγ, IL-2, and GM-CSF in splenocytes ( VanDenBerg et al, 2017 ). It has been also demonstrated that As 2 O 3 inhibited IFN-α secretion in plasmacytoid dendritic cells ( Ye et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cell culture study shows that the chemotherapeutic agent arsenic trioxide could inhibit early T cell cytokine production. [ 7 ]. Negative associations have been found between urine arsenic levels and proliferative response to phytohemaglutinin stimulation, CD4, CD4/CD8 ratio, and IL-2 secretion levels in children [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic exposure was been shown to down-regulate gene expression of IL-1β in human and animal cells via inhibition of TLR/IL-1 receptor and NF-κB signaling 6 . Other cytokines, including TNFα, INFγ, IL-2, IL-6, IL-8, IL-10, and IL-17A, are also interrupted by arsenic 6 , 49 , 50 . In macrophages, arsenic inhibits phagocytosis and NO production for digestion of exogenous antigens but induces apoptosis 51 .…”
Section: Discussionmentioning
confidence: 99%